Characteristics of the blood plasma “lipid peroxidation — antioxidant protection” system depending on nasal mucosa microflora composition in various chronic rhinitis phenotypes - O. V. Smirnova; N. S. Goncharova (Инфекция и иммунитет)
Chronic rhinitis is the most common ENT disease. Over the past decade, there has been an increased incidence of chronic rhinitis. In all forms of chronic rhinitis, there is a decrease in the protective properties of nasal mucous membrane, which can be accompanied by activation of nasal bacterial microflora. Dysbiosis of nasal mucous microbiota contributes to the development of inflammation, activation of immune cells with the development of immune reactions, activation of lipid peroxidation processes and changes in the activity of antioxidant defense factors in nasal cavity and blood. There is evidence that different phenotypic variants of chronic rhinitis are characterized by own specific spectrum of microorganisms in the nasal cavity, which significantly affects the course of diseases, as well as the state of the lipid peroxidation — antioxidant protection (LPO–AOP) system. The aim of our work was to comparatively assess quantitative composition of the microbial flora and indicators of the LPO–AOP system in patients with various forms of chronic rhinitis. The article presents the results of a laboratory examination of 165 patients with chronic rhinitis, including 45 patients with chronic allergic rhinitis, 49 patients with chronic vasomotor rhinitis, 32 patients with chronic atrophic rhinitis, and 39 patients with chronic infectious rhinitis. The control group consisted of 40 apparently healthy donors. In accordance with the study design, at the first stage, all subjects underwent a bacteriological examination of nasal mucous membrane and a quantitative assessment of the isolated microflora representatives. At the second stage, the LPO–AOP indices were determined in the blood plasma using a spectrophotometric method. Statistical analysis of the obtained results was performed using the Statistica 8.0 software package. To assess differences in the groups, the Kruskal–Wallis, Mann–Whitney, and Wilcoxon nonparametric tests were used. The critical level of statistical significance for testing scientific hypotheses was considered equal to p 0.05. The data are presented as a median (Me) and interquartile range (Q25–Q75). Changes in nasal mucosa microbiome induce a decrease in the activity of antioxidant defense factors in all studied phenotypic forms of chronic rhinitis. In cases of chronic allergic, vasomotor and infectious rhinitis, a significant increase in the level of both primary and secondary lipid peroxidation products is observed. Studies show that the greatest increase in lipid peroxidation activity is recorded in chronic infectious rhinitis, as well as the greatest nasal mucosa dysbiosis is revealed in this phenotype. Thus, the leading pathogenetic mechanism in chronic rhinitis is presented by hypoxia due to intermittent nasal congestion, which contributes to changes in the LPO–AOP system. At the same time, activated microbial flora also contributes to aggravation of such changes.